Grade-of-service-based routing in optical networks. - Szymanski, Andrzej (IEEE Communications magazine)
Optical networks serve an increasing number of services, each having different requirements. This necessitates the evolution towards routing algorithms that cover all aspects of quality. This article presents a tutorial overview and comparison of grade-of-service-based routing strategies, with emphasis on mechanisms that provide differentiated call-blocking probability for different classes of lightpath requests.